Cartografia escolar, multimodalidade e multiletramentos para o ensino de geografia na contemporaneidade - Batista, Natália Lampert (2019)
The present thesis presented as a research problem the need to understand and approximate the "usual cartography" present in the free software to the contents of the cartography of the Classroom Geography classes. Based on this problem, the discussion of the concept of a hybrid and multimodal map for the teaching of Geography and School Cartography in Basic Education was raised. The general objective of the proposal was to map the hybrid and multimodal maps, emphasizing its importance in School Cartography and developing methodologies based on the multiliteracies for the teaching of Contemporary Geography. Specifically, we aimed to: (1) Understand the evolution process of Cartography as language and multiple language through moments of its history that contribute to the understanding of hybrid and multimodal maps; (2) Identify characteristics in the teaching-learning process of school geography, in the context of cartographic multiletrations, to understand the concept of hybrid and multimodal maps; (3) Elaborate criteria that turns enable methodologies for teaching Geography and School Cartography in front of multi-mapping and hybrid and multimodal maps; (4) Develop and test multilevel methodologies for School Cartography that emphasizes the existence of hybrid and multimodal maps and that provides subsidies to multilevel pedagogical practices in the teaching of Geography in Basic Education. For this, the cartographic method of Deleuze and Guattari (1995) was used, investigating the history of Cartography and the emergence of hybrid and multimodal maps, verifying and proposing ways to use them in the classroom (having the discipline of Geography as focus on multimodality and multi-layering). Based on what has been exposed throughout the thesis, it is pointed out that hybrid and multimodal maps are a form of communication and structuring of spatial thinking and that permeate the discussion about how and why geographic space is mapped, capable of approaching multilevel cartographic practices , present in the free softwares, to the content of the School Cartography in the teaching of Geography in the classroom. In addition, they provide technical-scientific subsidies for the new generation of students, who are already born in the world of New Information and Communication Technologies, understand the strategies of multiletramentos in the teaching of Geography for the construction of their citizenship, a critical- reflective and guided in the understanding of the predominant intentionalities in the geographic space and its forms of representation, as well as to stimulate the spatial reasoning so as to be more forceful in the understanding of the categories of analysis of Geography. Therefore, in order to think of School Cartography in the teaching of Geography in contemporary times we can not ignore the pedagogy of multileraces and multimodality, and therefore hybrid and multimodal maps.